Metacognitive Strategies Used By English Department Students in Argumentative Essay Writing - Nugrahani, Wahyu Artikasari (RETAIN, 2021)
Writing has been a complex language skill to attain by students. In the EFL context, writing is more complicated because students need to consider the appropriate language to express their ideas in a foreign language. Therefore, they use writing strategies to assist them in solving their writing difficulties. However, little qualitative research had done to explore the metacognitive strategies used by undergraduate students, especially in English Department, in the EFL context. Thus, the present study attempted to describe how the students used metacognitive strategies in their argumentative essays writing. The subjects of this study were four English Department students of one of the state universities in Surabaya, which has an Expository and Argumentative Essay Writing class. The data were collected through semi-structured interview so that the students could willingly elaborate their answers. The result showed that the students had various ways of using metacognitive strategies. For planning strategies, all of the students decided the topic for their essay and read some source materials before developing the outline and made an outline, while one of them also used mapping. For monitoring strategies, all the students tried to manage their time to complete their essays. They also re-read their pieces before and after they finished them. It was to make sure the goals they set were achieved and the contents of their essays related to the topics. Lastly, for evaluating strategies, all of the students got feedback from their lecturers, and some of them also sought input from their peers. They also assessed their strategy and decided to stick to them even though they still had writing difficulties.